Proyecto de implementación de integración ASBANC para Peoplesoft Campus Solutions - Tokuda Oyafuso, Javier Arturo (2018)
The integration project with the Educational ERP PeopleSoft Campus Solutions for the educational group arises with the need to implement a solution that can improve the collection process due to the delay of one day so that it can be reflected in the system and the high load operative that was generated in enrollment periods. Since the payment is a requirement for the student to enroll, manual processes of validation of payments were generated. This meant additional costs for people who could serve the students and verify their payments and transactions with the bank. The project contemplated an initial stage of analysis where different alternatives that could cover this requirement were evaluated. Subsequently, it was decided to integrate the academic ERP with the service of provider "ASBANC" called "Transactional Facilitator of Collections" that allowed to review debt and make online payments with more than one bank with the same web service. The results obtained with the implementation of this solution were highly favorable. On the one hand, for the financial area, since it would no longer incur additional expenses in personnel that validates banking transactions. On the other hand, for the academic area, because the payments directly impacted on the undergraduate enrollment making the process cumbersome and causing discomfort in the students. Finally, for the students, their payments could be made just before enrollment without having an impact on their registration turn.